ASTROINFORMATICS AS A NEW RESEARCH FIELD: UKRVO AND VIRGO RESOURCES - Vavilova, I. B. (Одеські астрономічні публікації, 2016)
ABSTRACT. The data-oriented astronomy has allowed classifying the Astroinformatics as a new academic research field, which covers various multi-disciplinary applications of the e-Astronomy. Among them are the data modeling, data mining, metadata standards development, data access, digital astronomical databases, image archives and visualization, machine learning, statistics and other computational methods and software for work with astronomical survey and catalogues with their teta- topeta-scale astroinformation resource. In this review we describe briefly the astroinformatics applications and software/services performed for different astronomical tasks in frame of the VIrtual Roentgen and Gamma Observatory (VIRGO) and Ukrainian VirtualObservatory (UkrVO). Among them there are projects based on the archival space-born data of X-ray and gamma space observatories and on the Joint Digitized Archive (JDA) database of astroplate network collections. The UkrVO JDA DR1 deals with the star catalogues (FON, Polar zone, open clusters, GRB star fields) as well as the UkrVO JDA DR2 deals with the Solar System bodies (giant and small planets, satellites, astronomical heritage images).